2012
DOI: 10.1007/s12274-012-0202-9
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization, accumulation and trafficking of double-walled carbon nanotubes in human prostate cancer cells

Abstract: The carbon nanotubes (CNT) complexes (RNA-wrapped, oxidized DWNT) were endocytosed by capture in clathrin-coated vesicles, revealed by clear co-localization with both clathrin and transferrin. CNT complexes were also found in early endosomes, which was confirmed by co-localization with early endosome antigen (EEA). CNT complexes were not sorted for recycling back to the cell membrane (via fast recycling endosomes), as co-localization with Rab 4 was not observed.Instead, the overlapping of CNT complexes with bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…A strong, locally confined Raman signal was detected within the whole cell, confirming successful DWNT uptake and possible localization within endosomes, as also reported in previous work by our group, which has looked at the intracellular distribution of functionalized DWNTs in greater detail [19,20]. An important factor for the design of DWNTs as a nano-vector is that they do not significantly modify the cell environment, so that perturbations due to the payload can be detected.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…A strong, locally confined Raman signal was detected within the whole cell, confirming successful DWNT uptake and possible localization within endosomes, as also reported in previous work by our group, which has looked at the intracellular distribution of functionalized DWNTs in greater detail [19,20]. An important factor for the design of DWNTs as a nano-vector is that they do not significantly modify the cell environment, so that perturbations due to the payload can be detected.…”
Section: Resultssupporting
confidence: 84%
“…Furthermore, as we have shown in previous studies, they are released from the cells within 24 hours after having fulfilled their task and do not accumulate within cells [20]. In this study we investigated whether oxDWNT-RNA causes any changes in the cell biochemistry within this time frame, which they did not (figure 4).…”
Section: Discussionmentioning
confidence: 86%
“…Biocompatibility of CNTs with cardiac muscle cells has been tested revealing the lack of any observable cytotoxicity [71]. Uptake of CNTs was revealed to occur by a similar mechanism to that of nanoparticles [72]. Oxidized CNTs were encapsulated by RNA and the complex was internalized to cells by an endocytosis pathway.…”
Section: Two-dimensional Nanoarchitectures From Carbon Nanotubes For mentioning
confidence: 99%
“…Heister [78,79,196] and Neves [197,198] have demonstrated that CNTs functionalized with polyethylene glycol (PEG) or ribonucleic acid (RNA) can be used to detect cancer cells within biological systems. Such carbon nanomaterial systems can be used for targeting tumor cells and delivering drugs for future cancer theranostics.…”
Section: Applicationsmentioning
confidence: 99%